PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK PADA KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE XIAOMI - Wirawan, I Putu Gede Agi Agata; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 10 No 5 (2021)DO - 10.24843/EJMUNUD.2021.v10.i05.p01, 2021)
The development of technology is growing rapidly, so that smartphones are common and an effective communication tool for users to meet all their needs and interests. Many manufacturers provide smartphone products that offer various conveniences. There are several considerations for consumers in buying a product such as price, brand image and product quality. Purpose of this study is to determine the effect of price, brand image and product quality on purchasing decisions. Research was conducted in Denpasar and the population in this study are consumers who had bought or used Xiaomi smartphone. The research sample consisted of 120 respondents with purposive sampling. Data are analyzed using multiple linear regression. results show that price has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions and product quality has a positive and significant effect on purchasing decisions o Xiaomi smartphones in Denpasar. Keywords: Price, Brand Image, Product Quality, Purchase Decision